Meaning and reference - Moore, A. W., 1956- (Oxford ; New York : Oxford University Press, 1993)
"The aim of this series is to bring together important recent writings in major areas of philosophical inquiry, selected from a variety of sources, mostly periodicals, which may not be conveniently available to the university student or flee general reader. The editor of each volume contributes an introductory essay on the items chosen and on the questions with which they deal. A selective bibliography is appended as a guide to further reading." "This volume presents a selection of the most important writings in the debate on the nature of meaning and reference which started at the end of the nineteenth century with Frege's classic essay 'On Sense and Reference'. This subject lies at the very heart of the philosophy of language."--BOOK JACKET.
Introduction / A. W. Moore -- On sense and reference / Gottlob Frege -- Letter to Jourdain / Gottlob Frege -- Descriptions / Bertrand Russell -- On referring / P. F. Strawson -- Mind and verbal dispositions / W. V. Quine -- Truth and meaning / Donald Davidson -- On the sense and reference of a proper name / John McDowell -- What does the appeal to use do for the theory of meaning? / Michael Dummett -- Meaning and reference / Hilary Putnam -- Identity and necessity / Saul Kripke -- Putnam's doctrine of natural kind words and Frege's doctrine of sense, reference, and extensions : can they cohere? / David Wiggins -- The causal theory of names / Gareth Evans -- Frege's distinction between sense and reference / Michael Dummett -- Wittgenstein on following a rule / John McDowell.
Includes bibliographical references (p. [296]-300) and index.
Keywords: Meaning (Philosophy); Reference (Philosophy); Language and languages -- Philosophy; Meaning (philosophy); Meaning